The state of national electronic prescription systems in the EU in 2018 with special consideration given to interoperability issues - Bruthans, Jan (International journal of medical informatics, 2020)
INTRODUCTION: The electronic prescribing system (EPS) is now widely used in the USA and largely also in EU member countries. Nevertheless, comparisons of different EPS are very scarce. Whilst the EU strives for cross-border interoperability in healthcare, the aim of this study is to provide a contemporary account of the state of national EPS in such countries. METHODS: For the sake of consistency the state of each of the EPS as of the end of 2018 was researched using an e-mail questionnaire. Respondents were chosen from among authors who have previously published studies on electronic prescriptions. RESULTS: Data on EPS was gathered from 23 out of the 28 EU member states. In 2018 EPS was in daily use in 19 EU states, and one further country had a pilot project, whereas the remaining 3 were only at the planning stage. Most of the EPS do not differ significantly in basic design, however authentication procedures vary substantially. DISCUSSION: There is a significant increase in EPS usage in EU countries as compared with previous studies. Cross-border interoperability in the EU is still limited, and further advancement might be hampered by differences in authentication procedures. CONCLUSION: Although it was not possible to acquire data from all the EU countries, this study shows the present state of electronic prescription in most of them and demonstrates continuous development in this area.
Keywords: Information system; pilotní projekty; Electronic Prescribing; Interoperability; Drug prescription; European Union; Pilot Projects; elektronické předepisování; Evropská unie; Electronic prescription